Idiom Translation Strategies in Bee Movie - Murtajib, Muhammad Rizki; Wahyuningsih, Neneng Sri (e-LinguaTera, 2024)
Idiomatic expressions, commonly referred to as idioms, are sentences with figurative meaning—a meaning that differs from the literal meaning of the idiom's constituent parts and does not always mean what the words state. This study aims to examine the idiom translation techniques used in the English to Indonesian subtitles of Bee Movie. The movie comes from Apple TV because the quality control process is applied to the subtitles before they are broadcast. Using Baker's theory of idiom translation techniques, this paper is studied. These tactics include adopting idioms from the source language, translating by paraphrasing, translating by omitting a play on idiom, translating by omitting a whole idiom, and utilizing an idiom with a similar meaning but a different form. The data in this study are identified and analyzed using a descriptive qualitative method. 42 idiom data were discovered based on the movie's data. Of those 42 data, 41 data (93%) contain translation methods for paraphrases, and one datum (7%) contains translation strategies for borrowing. In light of the research's conclusions, it is advised that translators possess a solid grasp of both Indonesian and English idioms in order to employ a variety of idiom translation strategies.